Big business stability and social welfare - Fogel, Kathy 1974-; Morck, Randall; Yeung, Bernard 1953- (NBER working paper series, 2008)
"Many countries appear to have excessively stable big business sectors, in that higher rates of big business turnover have been correlated with faster economy growth. Public policies that stabilize big business sectors are sometimes justified as supportive of social objectives. We find no consistent link between big business stability and public goods provision, egalitarianism, or labor empowerment. While absence of evidence is not evidence of absence, these findings suggest that other explanations, such as special interest politics or behavioral biases favoring the status quo also be considered"--National Bureau of Economic Research web site